2023
DOI: 10.1037/ser0000714
|View full text |Cite
|
Sign up to set email alerts
|

Veterans’ reasons for dropping out of prolonged exposure therapy across three delivery modalities: A qualitative examination.

Abstract: Premature dropout from posttraumatic stress disorder treatment (PTSD) hinders treatment response. Studies have primarily used quantitative methodology to identify factors that contribute to Veterans’ premature dropout, which has yielded mixed results. Qualitative methods provide rich data and generate additional hypotheses about why Veterans discontinue PTSD treatment. This study aimed to understand Veterans’ reasons for dropping out of prolonged exposure therapy (PE) and to examine if there are differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…As participants moved into the active components of treatment, PTSD− and PTSD+ completers generally expressed self-efficacy in being able to engage in the tasks of treatment, whereas discontinuers expressed less self-efficacy. A previous study also found that some discontinuers of PE expressed low self-efficacy in being able to handle the difficult emotions involved in therapy (Wells et al, 2023). In the present study, many discontinuers described their doubt as contributing to their decision to discontinue treatment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As participants moved into the active components of treatment, PTSD− and PTSD+ completers generally expressed self-efficacy in being able to engage in the tasks of treatment, whereas discontinuers expressed less self-efficacy. A previous study also found that some discontinuers of PE expressed low self-efficacy in being able to handle the difficult emotions involved in therapy (Wells et al, 2023). In the present study, many discontinuers described their doubt as contributing to their decision to discontinue treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Yet little is known about how treatment-related cognitions during treatment may impact treatment outcomes. Treatment-related beliefs and interpretations that have been related to early discontinuation include low buy-in to the treatment rationale early in treatment (Hundt et al, 2020;Taylor, 2003), perceptions that ongoing symptoms mean treatment is not working (Kehle-Forbes et al, 2022), worry that treatment will have a negative impact on functioning (Kehle-Forbes et al, 2022), low selfefficacy in being able to handle the difficult emotions involved in therapy (Wells et al, 2023), and perceptions that treatment is not worth the distress involved (Hundt et al, 2017(Hundt et al, , 2020. A few studies have also examined relationships between treatment-related beliefs and symptom response.…”
mentioning
confidence: 99%
“…Studies highlighted patients’ interpersonal difficulties with clinical staff and, in group-based interventions with their peers, as factors influencing engagement in treatment and outcomes. 70 , 82 , 91–93 At times these gave rise to patient feelings of disconnection and invalidation. 80 I was pissed off that people were trying to desensitize me to something horrible that happened because it almost seems like, ‘Oh you’re overreacting just think about, just be around it enough and you won’t feel that way anymore.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, safety, privacy, and comfort could create conditions that facilitate the therapeutic process, while on the other hand, avoidance can interfere with treatment outcomes and can maintain PTSD symptoms. Reducing avoidance while supporting engagement is particularly important for couples-based PTSD treatment; given studies have found that 30–48% of veterans drop out from cognitive behavioral conjoint therapy (Morland et al, 2022; Pukay-Martin et al, 2021) and that avoidance is associated with dropout from trauma-focused PTSD treatment (Wells et al, 2023). Clinicians may discuss at the outset of therapy how to create a safe therapy environment while also considering how to minimize avoidance.…”
Section: Discussionmentioning
confidence: 99%